THC degradation does not impair the accuracy of THC doses aerosolized by the metered-dose SyqeAir inhaler: a 24-month stability trial - Joshua Aviram; Daniella Atzmony; Anna Frenklakh; Asaf Kroll; Ilana Zaks; Arno Hazekamp (Journal of Cannabis Research)
Abstract Background Although the worldwide use of medical cannabis (MC) is on the rise, there is insufficient data regarding the long-term stability of phytocannabinoids in the plant material under different storage conditions. Specifically, there is insufficient data on the effect of storage conditions on the availability of (-)-∆9-trans-tetrahydrocannabinol (THC) in vaporized cannabis. The Syqe inhaler delivers metered doses of phytocannabinoids by inhalation and utilizes accurate quantities of ground cannabis inflorescence packaged in tamper-proof cartridges. We aimed to assess the stability of phytocannabinoids in ground cannabis before and after packaging in Syqe cartridges as well as the reproducibility of THC delivery in the aerosolized dose. Methods Ground MC inflorescence was stored under different temperature and humidity conditions, before or after being packaged in Syqe cartridges. Concentrations of the major phytocannabinoids therein were analyzed at different time points using ultra-high performance liquid chromatography (U-HPLC). THC doses aerosolized via the Syqe inhaler were evaluated using cartridges stored for up to 2 years at 25°C. Every vapor chip contains 13.5±0.9 mg of ground MC powder. Results No significant changes were observed in phytocannabinoid concentrations in ground cannabis inflorescence after 3 months of bulk storage in a polypropylene container and sealed in an aluminum foil pouch at 5°C. In contrast, significant changes in phytocannabinoid concentrations were found when ground inflorescence was stored in the cartridges at 25°C for 2 years. Specifically, CBGA, THCA, and total THC concentrations decreased from 0.097±0.023, 2.7±0.3, and 2.80±0.16 mg/chip at baseline to 0.044±0.007 (55% decrease), 1.50±0.27 (44% decrease), and 2.20±0.083 (21% decrease) mg/chip following 2 years, respectively, while CBN and THC concentrations increased from 0.005±0.005 and 0.44±0.11 mg/chip at baseline to 0.14±0.006 (2700% increase) and 0.88±0.22 (100% increase) mg/chip following 2 years, respectively. Storage at 30°C revealed a steeper change in phytocannabinoid concentrations within an even shorter period. Despite the significant change of relative cannabinoid composition within the cartridge, the actual THC dose present in the aerosol remained relatively stable throughout this period and within the dosage range of 500mcg±25% required for pharmaceutical-grade inhalers. Conclusions MC powder in Syqe cartridges may be stored at room temperature for at least 2 years after production without affecting the aerosolized THC dose delivered to patients by more than ±25%. Future studies should analyze additional phytocannabinoids and terpenes in the cannabis inflorescence and assess the stability of different cannabis cultivars following storage in Syqe cartridges.